DISCUSSING RESEARCH METHODS IN SUFISM - Nur Annisa Istiqomah; Zulfi Mubarok; Mohammad Asrori; Ahmad Nurul Kawakip (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2024)
This article discusses three things; first, the paradigm of the study of research methods in Sufism; second, the factors that influence it; and third, its implications for the thoughts of Muslims. The method used in this research is library research with a text research approach based on Harold Lasswell's theory. The data collection is done using literature analysis (content analysis technique). Some of the research findings found include: First, the paradigm of Sufism research methods has three forms: bayani method, burhani method, irfani method. Second, internally, three factors influence it: first, the desire to understand and practice Sufism; second, the need to answer theoretical and practical questions, and third, the desire to preserve Sufism knowledge. Externally, three factors influence it: first, culture and politics; second, science and technology, and third, intellectual tradition and globalization.damage. The conclusion that this article shows is that the Sufism Research Method serves to enrich the treasures of the Islamic community.